Transnational labour solidarity in (the) crisis - Bieler, Andreas (Escarpment Press, 2014)
The global financial crisis as part of globalisation has put labour movements under pressure around the world. This poses yet again the question of transnational solidarity. As a result of uneven and combined development, individual labour movements find themselves in rather different positions with contradictory interests. The purpose of this article is to assess conceptually possible labour strategies towards transnational solidarity against the background of the structuring conditions within the global economy.